2004
DOI: 10.1097/01.alc.0000145789.55183.d4
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Receptor Gene (TAS2R38), 6‐n‐Propylthiouracil (PROP) Bitterness and Alcohol Intake

Abstract: These results support taste genetic effects on alcohol intake. PROP bitterness serves as a marker of these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
287
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(329 citation statements)
references
References 55 publications
27
287
2
4
Order By: Relevance
“…While the exact mechanism of phenotypic variation is unknown, characterization of bitter tasting sensation has been linked to several adverse health affects. Nontasters have shown an increased risk of alcoholism, 110 higher body mass index in women, 111 and dental caries in children, 112 while super taster males may have an increased risk of colon cancer. 113 Furthermore, the PROP-insensitive T allele (T785C) of TAS2R38 has been associated with eating behavior.…”
Section: Genetic Chemosensory Variationmentioning
confidence: 99%
“…While the exact mechanism of phenotypic variation is unknown, characterization of bitter tasting sensation has been linked to several adverse health affects. Nontasters have shown an increased risk of alcoholism, 110 higher body mass index in women, 111 and dental caries in children, 112 while super taster males may have an increased risk of colon cancer. 113 Furthermore, the PROP-insensitive T allele (T785C) of TAS2R38 has been associated with eating behavior.…”
Section: Genetic Chemosensory Variationmentioning
confidence: 99%
“…164 In addition to sweetness, genotype–phenotype studies in humans suggest that ethanol stimulates at least one bitter receptor. 165 Alcohol may also stimulate receptors for the common chemical sense, at least in rodents. 166 Alcohol also has an odor, andalthough the exact receptors are not known, based on other typical molecules, it is likely to stimulate several different receptors; the patterns of receptor activation may differ based on concentration.…”
Section: Alcohol Perceptionmentioning
confidence: 99%
“…7,10,11 The relevant role of genetic factors both on alcohol consumption and dependence has been clearly demonstrated by genome-wide association study (GWAS) studies. [12][13][14][15][16] Moreover, studies on the genetic variations in bitter taste receptors have also shown that variations in TAS2R16 and TAS2R38 genes can influence alcohol intake [17][18][19] but not dependence. 19 On the contrary, very little is known about the possible contribution of genetic factors to alcohol preferences in humans.…”
Section: Introductionmentioning
confidence: 99%